Spina bifida detection in first trimester ultrasound - Teixeira,Eliana (2018)
Spina bifida is one of the most common severe congenital defects of the central nervous system. Prenatal diagnosis is currently performed in second trimester. First trimester diagnosis is rare and can be challenging, but it can be suspected in the absence of intracranial translucency. We report images of a case of spina bifida detected at 13 weeks scan. The fetus presented images suggestive of open spina bifida and intracranial translucency was absent, also the crown-rump length evolution in serial ultrasound examinations was deficient. At 16 weeks a spontaneous abortion occurred and the histopathology analysis confirmed the diagnosis of spina bifida.